2017
DOI: 10.3855/jidc.9338
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic typing of enteropathogenic Escherichia coli isolated in childhood acute diarrhea in Abuja, Nigeria

Abstract: Introduction: Enteropathogenic Escherichia coli (EPEC) causes infectious diarrhea among children in developing countries. However, in Nigeria, due to limited laboratory resources, the genetic diversity of its virulence factors, which include intimin subtypes, remains undefined. Methodology: EPEC isolates from diarrheic children 60 months of age and younger in Abuja, Nigeria, were analyzed. Polymerase chain reaction (PCR) for EPEC virulence gene, Hep-2 cell adherence, and serotyping were performed. EPEC strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…Atypical EPEC strains carrying LEE genes including eae, but lacking bfpA gene, were isolated from seven cases and 16 controls. EPEC have been historically prominent in Nigeria, 14,16 based on reports from studies that used serotyping but more recent studies using hybridization, 17 and PCR, [18][19][20]56,57 like our current WGS study have found this pathotype much less common suggesting that earlier results may be due to methodological artefacts. Shigella has been reported as a principal etiological agent of diarrheal disease in African countries and has consequently been prioritized for vaccine development.…”
Section: Chattaway Et Al (2013)mentioning
confidence: 70%
“…Atypical EPEC strains carrying LEE genes including eae, but lacking bfpA gene, were isolated from seven cases and 16 controls. EPEC have been historically prominent in Nigeria, 14,16 based on reports from studies that used serotyping but more recent studies using hybridization, 17 and PCR, [18][19][20]56,57 like our current WGS study have found this pathotype much less common suggesting that earlier results may be due to methodological artefacts. Shigella has been reported as a principal etiological agent of diarrheal disease in African countries and has consequently been prioritized for vaccine development.…”
Section: Chattaway Et Al (2013)mentioning
confidence: 70%
“…The presence of the mcr-1 gene in these strains is of concern because it is pathogenic to humans, posing a public health risk. The use of antimicrobials to treat infections caused by the EPEC and STEC pathotypes is recommended only in severe cases (Wong et al 2012, Ifeanyi et al 2016. As colistin has been cited as a last resort for the treatment of multidrugresistant bacteria, resistance to this antimicrobial is very important, as it may be a limiting factor for the successful treatment of infections.…”
Section: Epec and Stec Characterizationmentioning
confidence: 99%
“…The Enteropathogenic Escherichia coli (EPEC) and Shigatoxigenic E. coli (STEC) strains are pathogens of public health importance due to their ability to cause enteric diseases in humans (Ifeanyi et al 2016, Fierz et al 2017, Torres 2017) these pathogens are isolated from poultry and poultry products (Dutta et al 2011, Alonso et al 2012, Samanta et al 2015, Doregiraee et al 2016, Badi et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies worldwide have reported on ESBL resistance in E. coli from stool of diarrheic children [5,14,[21][22][23][24][25][26][27][28][29]. There are few reports in Nigeria on ESBL production in E. coli isolated from stool of diarrheic patients [30][31][32][33][34]. However, no report is known to us on ESBL and AmpC βlactamase resistance in E. coli from diarrheic patients of any age group in the study area.…”
Section: Introductionmentioning
confidence: 99%